Andrographis paniculata nees and Orthosiphon stamineus benth ground leaf as antibiotic and antioxidant supplements for broiler chicken (Call No ITA 2014 12) - Malahubban, Masnindah (2014)
The use of synthetic antibiotics and antioxidants has creates serious obstacles and hazards, to farmers, consumers and the environment. Antibiotics and antioxidant from natural sources can potentially be useful to overcome these problems. Therefore, present study was conducted to evaluate the selected medicinal plants, Andrographis paniculata and Orthosiphon stamineus for antibiotics and antioxidant potential and subsequently to evaluate the broiler performance by inclusion the A. paniculata and O. stamineus ground leaf in diets. Initially, A. paniculata and O. stamineus ground leaf were evaluated for their in vitro antibiotic and antioxidant potential by extracting the ground leaf in four solvents, namely water, methanol, ethanol and chloroform and subsequently testing using the disc diffusion method for antibiotic potential and selected radical scavenging activities for antioxidant potential. Qualitative screening for bioactive compound on both extracts by using methanol as solvent has indicated the presence of alkaloid, saponin, flavonoid, tannin, terpenoid and steroid. High performance liquid chromatography analysis indicated that andrographolide and rosmarinic acid were the major compound from A. paniculata and O. stamineus, respectively. It was found that the highest yields of these two compounds were obtained by methanol extraction and that substantial antibiotic and antioxidant properties were exhibited by these compounds. In addition, it was showed that the O. stamineus extract contained higher antioxidant capacity than A. paniculata extract. The ground leaf were incorporated in broiler diets at levels of 0, 2, 4, and 8 g/kg and the influence on growth performance, carcass characteristics,serum biochemistry, and intestinal and liver morphology was examined in a 42-d feeding trial. It was involved 280 one-day old male broiler chickens,grown, maintained and received ad libitum water and diet. The feeding trial was started from 21 days old and assigned with respective treatments. At day-42, the broiler chickens were slaughtered and analysed and it was found that broilers fed O. stamineus ground leaf at a rate 8 g/kg was the most promising dietary supplement to promote overall growth performance without deleterious effects on carcass characteristics, serum biochemical properties and morphological components of liver and intestine compared with A.paniculata ground leaf and control diets. In addition to promoting weight gain,it reduced abdominal fat and serum cholesterol. It also maintained the integrity of liver, thus indicating that no toxic effect from O. staminues supplementation at a rate up to 0.8 g/kg. Besides that, 8 g/kg O. stamineus supplementation improved intestinal structure, especially in the duodenum. Present study also found that the inclusion of O. stamineus ground leaf at 8 g/kg in the broiler diet increased total tract N retention and apparent metabolizable energy. Based on these results, O. stamineus ground leaf at 8 g/kg was selected for the next in vivo experiment. Present study was conducted to evaluate the response of broiler due to antibiotic and antioxidant properties of O.staminues by comparing its potential with tetracycline and Vitamin E supplementation in diets, as positive controls. The study was involved 160 of a one-day old male broiler chickens, and had ad libitum water and feed for up to 20-day old. The respective treatments were assigned and initiated at 21-day old male broiler chickens. After slaughtering, data were recorded and analysed at 42-day old male broiler chickens, and it was found that O.stamineus ground leaf supplement at a rate of 8 g/kg in broiler diet results in growth performance similar to that of tetracycline and Vitamin E supplementation. In addition, it was also found that 8 g/kg O. stamineus supplementation in diet promoted serum enzymes-lowering effect. In contrast, high serum enzymes activity showed in broiler fed tetracycline supplement. The inclusion of 8 g/kg O. stamineus ground leaf in diet of broiler enhanced meat quality by stabilizing sensory properties, meat colour and meat pH. The results also indicated that the inclusion of O. stamineus leaf ground at 8 g/kg in diet was comparable with 200 mg/kg Vitamin E supplementation in diet. It was found that all dietary treatments maintained intestinal population of Lactobacillus and Escherichia coli. However, the inclusion of 8 g/kg O. stamineus or tetracycline in diet inhibited the population of facultative anaerobe. Therefore, the use of O. stamineus ground leaf as supplement in broiler chicken diet has the potential to promote and maintain growth and gut health and subsequently creates safe and sustainable broiler chicken production.